All-solid-state composite electrode and preparation method thereof
The all-solid-state composite electrode is prepared by solvent dispersed carbon material and vacuum suction filtration, which solves the problems of uneven dispersion and adhesive obstacles in dry preparation, and achieves efficient electrochemical performance and long-life all-solid-state battery.
Patent Information
- Application Number
- CN202510718322.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-29
AI Technical Summary
During the dry preparation process of all-solid-state composite electrode, there are problems such as uneven dispersion of active substances and electrolytes, poor electron and ion transmission networks, and polymer binders hinder lithium transmission, resulting in attenuation of battery performance.
The solvent is used to disperse carbon materials, mix electrode active materials, solid electrolytes and carbon materials, and form a uniform slurry through ultrasonic and magnetic stirring. The all-solid composite electrode is prepared on the porous current collector by vacuum suction filtration and heating and drying to form a three-dimensional conductive network to avoid the use of polymer binder.
The uniform mixing of electrode active substances and electrolytes is achieved, the lithium transmission path is optimized, the conductivity and electron transmission are improved, the internal resistance of the battery is reduced, the energy density and cycle life are improved, the electrodes and electrolytes are ensured, and the battery life is extended.
Smart Images

Figure CN120565589A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode and a method for manufacturing the same, and in particular to an all-solid-state composite electrode and a method for manufacturing the same. Background Art
[0002] Due to the unique characteristics of solid-state electrolytes, all-solid-state composite electrodes are mostly produced using a dry process. This process results in uneven dispersion of the active material and electrolyte in the electrode, preventing the formation of an effective electron and ion transport network, which severely impacts battery capacity. Furthermore, the use of polymer binders can hinder lithium transport across the electrode surface, leading to high interfacial impedance, limited contact between the active material and the electrolyte, and consequently, reduced battery performance. Summary of the Invention
[0003] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing an all-solid-state composite electrode that is low-cost, safe and environmentally friendly. Another purpose of the present invention is to provide an all-solid-state composite electrode that has high energy density and long cycle life.
[0004] Technical solution: The method for preparing an all-solid-state composite electrode according to the present invention comprises the following steps:
[0005] Step 1: dispersing the carbon material with a solvent to obtain a carbon material dispersion;
[0006] Step 2: mixing the electrode active material, solid electrolyte and carbon material dispersion according to the mass ratio, and stirring them by ultrasonic and magnetic force to obtain a uniform slurry;
[0007] Step three: After vacuum filtration of the slurry on the porous current collector, heating and drying, and roller pressing are performed to obtain an all-solid-state composite electrode.
[0008] Furthermore, in step 1, the solvent is one or more of pentane, hexane, heptane, toluene, p-xylene, chlorobenzene, benzene, acetonitrile, N-methylpyrrolidone, ethers, ethanol, and water.
[0009] Furthermore, in step 1, the carbon material is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carboxylated carbon nanotubes, hydroxylated carbon nanotubes, fluorinated carbon nanotubes, graphene, carbon fibers, and fullerenes. The carbon material is preferably single-walled carbon nanotubes.
[0010] Furthermore, in step 2, the mass ratio of the electrode active material, the solid electrolyte, and the carbon material dispersion is 50-80:15-45.5:0.5-5.
[0011] Furthermore, in step 2, the electrode active material includes a positive electrode material and a negative electrode material, the positive electrode material is one or more of lithium-rich manganese-based materials, lithium iron phosphate, lithium manganate, nickel cobalt manganese ternary, lithium cobalt oxide, sodium vanadium phosphate, sodium iron pyrophosphate, Prussian compounds, sodium nickel iron manganate, and sodium copper iron manganate, and the negative electrode material is one or more of graphite, lithium titanate, silicon-based materials, soft carbon, hard carbon, selenium-based alloy materials, and tin-based materials.
[0012] Furthermore, in step 2, the solid electrolyte is an oxide-based solid electrolyte, a sulfide-based solid electrolyte or a halide-based solid electrolyte.
[0013] Furthermore, in step 2, the ultrasonic power is 100 to 1500 W, the ultrasonic time is 5 to 30 minutes, and the magnetic stirring time is more than 2 hours.
[0014] Furthermore, in step three, the porous current collector includes one or more of porous copper foil, porous aluminum foil, composite porous current collector, etc., and the pore size is 10 to 2000 microns.
[0015] Furthermore, in step three, the temperature of heating and drying is 60-120° C., the time of heating and drying is 3-12 hours, and the pressure of roller pressing is 3-15 MPa.
[0016] The all-solid-state composite electrode of the present invention comprises an electrode active substance, a solid electrolyte and a carbon material. The carbon material is cross-linked to form a three-dimensional conductive network, and the electrode active substance and the solid electrolyte are bound to the three-dimensional conductive network.
[0017] Preparation Principle: The all-solid-state electrode prepared by filtration allows for a uniform mixing of the active material and electrolyte, optimizing the lithium transport pathway. The combination of filtration and carbon materials not only improves conductivity and optimizes electron transport pathways, but also eliminates the need for binders in the preparation of solid-state electrodes while ensuring active contact between the electrode and electrolyte.
[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0019] 1. The preparation method is simple and efficient, the solvent can be recycled, the cost is low, and it is safe and environmentally friendly, and no polymer binder is required;
[0020] 2. The prepared all-solid-state composite electrode has uniform dispersion, close contact, and small porosity, which ensures the rapid transmission of ions and electrons and exhibits excellent electrochemical performance;
[0021] 3. No additional electrochemically inactive binder is introduced during the preparation of the all-solid-state composite electrode, which reduces the internal resistance of the battery. The use of porous current collectors effectively reduces the proportion of additional inactive substances, thereby improving energy density and cycle life.
[0022] 4. The use of crisscrossing carbon tubes to form a tough network tightly bound to the surface of the electrode particles reduces the cracking and pulverization of particles caused by stress concentration, ensures the contact between particles, effectively extends the service life of the battery, opens up a new path for the preparation of all-solid-state composite electrodes, and promotes the development of all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a preparation flow chart of the present invention;
[0024] Figure 2 1 is a cycle performance diagram of the all-solid-state composite electrode obtained in Example 1 of the present invention;
[0025] Figure 3 is a scanning electron microscope image of the all-solid-state composite electrode obtained in Example 1 of the present invention;
[0026] Figure 4 Schematic diagram of the bending of the all-solid-state composite electrode obtained in Example 1 of the present invention;
[0027] Figure 5 This is a cycle performance diagram of the all-solid-state composite electrode obtained in Comparative Example 1 of the present invention;
[0028] Figure 6 This is a cycle performance diagram of the all-solid-state composite electrode obtained in Comparative Example 2 of the present invention;
[0029] Figure 7 This is a cycle performance diagram of the all-solid-state composite electrode obtained in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0030] In the following examples, the materials and reagents used are commercially available unless otherwise specified. Experimental methods without specific conditions in the examples are generally performed under conventional conditions or those recommended by the manufacturer.
[0031] Example 1
[0032] like Figure 1 As shown, a method for preparing an all-solid-state composite electrode comprises the following steps:
[0033] (1) Weigh 0.1 g of single-walled carbon nanotubes and disperse them in 10 g of hexane solvent to obtain a carbon material dispersion.
[0034] (2) After ensuring uniform dispersion, the electrode active material, solid electrolyte, and carbon material dispersion were weighed in a mass ratio of 60:39:1. The electrode active material includes a positive electrode material and a negative electrode material. The positive electrode material is a lithium-rich manganese-based positive electrode, and the negative electrode material is lithium titanate. Subsequently, a uniform slurry was obtained by dispersing the mixture under 200W ultrasound for 10 minutes and magnetic stirring for more than 2 hours.
[0035] (3) After vacuum filtration of the slurry through the porous current collector using a vacuum filtration device, that is, after separating the solvent, the slurry was heated and dried at 80° C. for 8 h, and then roller pressed at 3 MPa to obtain an all-solid-state composite electrode.
[0036] like Figure 2 The all-solid-state composite electrode of this embodiment was subjected to a cycle performance test at a stacking pressure of 2 MPa and a rate of 0.2C at 30°C. The results showed that the capacity of the all-solid-state battery prepared by filtration did not decay after 50 cycles, indicating that the all-solid-state electrode prepared by filtration has better contact and charge transfer paths, and can improve the cycle life of the battery.
[0037] like Figure 3 , showing the microscopic morphology of the all-solid-state electrode prepared by filtration. The results showed that the solid electrolyte particles and electrode particles were evenly dispersed, and the carbon nanotubes were dispersed to form a three-dimensional network bound to the surface of the particles, which made the electrode have better mechanical properties without the use of binders.
[0038] like Figure 4 , demonstrating that the all-solid-state electrode prepared by filtration has good toughness and can adhere well to the porous current collector without the use of a binder.
[0039] The energy density of the all-solid-state composite electrode obtained in this example is 373Wh / Kg.
[0040] Example 2
[0041] A method for preparing an all-solid-state composite electrode comprises the following steps:
[0042] (1) Weigh 0.1 g of carbon nanofiber and disperse it in 10 g of toluene solvent to obtain a carbon material dispersion.
[0043] (2) After ensuring uniform dispersion, the electrode active material, solid electrolyte, and carbon material dispersion were weighed in a mass ratio of 50:45.5:0.5. The electrode active material includes a positive electrode material and a negative electrode material, with the positive electrode material being lithium iron phosphate and the negative electrode material being graphite. Subsequently, a uniform slurry was obtained by dispersion using 100W ultrasound for 30 minutes and magnetic stirring for 3 hours.
[0044] (3) After vacuum filtration of the slurry through the porous current collector using a vacuum filtration device, that is, after separating the solvent, the slurry was heated and dried at 60° C. for 12 h, and then roller pressed at 3 MPa to obtain an all-solid-state composite electrode.
[0045] Example 3
[0046] A method for preparing an all-solid-state composite electrode comprises the following steps:
[0047] (1) Weigh 0.1 g of hydroxylated carbon nanotubes and disperse them in 10 g of pentane solvent to obtain a carbon material dispersion.
[0048] (2) After ensuring uniform dispersion, the electrode active material, solid electrolyte, and carbon material dispersion were weighed in a mass ratio of 80:15:5. The electrode active material includes a positive electrode material and a negative electrode material, with the positive electrode material being lithium manganese oxide and the negative electrode material being lithium titanate. Subsequently, a uniform slurry was obtained by dispersion using 1500W ultrasound for 5 minutes and magnetic stirring for 2 hours.
[0049] (3) After vacuum filtration of the slurry through the porous current collector using a vacuum filtration device, that is, after separating the solvent, the slurry was heated and dried at 120° C. for 3 h, and then roller pressed at 15 MPa to obtain an all-solid-state composite electrode.
[0050] Example 4
[0051] A method for preparing an all-solid-state composite electrode comprises the following steps:
[0052] (1) 0.1 g of fullerene was weighed and dispersed in 10 g of acetonitrile solvent to obtain a carbon material dispersion.
[0053] (2) After ensuring uniform dispersion, the electrode active material, solid electrolyte, and carbon material dispersion were weighed in a mass ratio of 70:27:3. The electrode active material includes a positive electrode material and a negative electrode material. The positive electrode material is sodium nickel iron manganese oxide, and the negative electrode material is hard carbon. Subsequently, a uniform slurry was obtained by dispersing the mixture using 800W ultrasound for 17 minutes and magnetic stirring for 4 hours.
[0054] (3) After vacuum filtration of the slurry through the porous current collector using a vacuum filtration device, that is, after separating the solvent, the slurry was heated and dried at 90° C. for 8 h, and then roller pressed at 9 MPa to obtain an all-solid-state composite electrode.
[0055] The hard carbon in this embodiment can be replaced by any one of graphite, lithium titanate, silicon-based materials, soft carbon, hard carbon, selenium-based alloy materials, and tin-based materials. The sodium nickel iron manganate can be replaced by any one of lithium iron phosphate, lithium manganate, nickel cobalt manganese ternary, lithium cobalt oxide, sodium vanadium phosphate, sodium iron pyrophosphate, Prussian compounds, sodium nickel iron manganate, and sodium copper iron manganate.
[0056] Example 5
[0057] A method for preparing an all-solid-state composite electrode comprises the following steps:
[0058] (1) Weigh 0.1 g of fluorinated carbon nanotubes and disperse them in 10 g of p-xylene solvent to obtain a carbon material dispersion.
[0059] (2) After ensuring uniform dispersion, the electrode active material, solid electrolyte, and carbon material dispersion were weighed in a mass ratio of 75:23:2. The electrode active material includes a positive electrode material and a negative electrode material. The positive electrode material is sodium copper iron manganese oxide, and the negative electrode material is micron silicon. Subsequently, a uniform slurry was obtained by dispersion using 300W ultrasound for 20 minutes and magnetic stirring for 3 hours.
[0060] (3) After vacuum filtration of the slurry through the porous current collector using a vacuum filtration device, that is, after separating the solvent, the slurry was heated and dried at 80° C. for 5 h, and then roller pressed at 12 MPa to obtain an all-solid-state composite electrode.
[0061] Comparative Example 1
[0062] The remaining steps of this comparative example are the same as those of Example 1, except that the filtration is replaced by dry grinding. Figure 5 The results showed that the prepared all-solid-state battery only showed a discharge specific capacity of 151.95 mAh / g, and showed obvious attenuation after 50 cycles, indicating poor electrochemical performance.
[0063] Comparative Example 2
[0064] The remaining steps of this comparative example are the same as those of Example 1, except that the carbon nanotubes are replaced with conductive carbon black. Figure 6 The results showed that the prepared all-solid-state battery only showed a discharge specific capacity of 128.31 mAh / g, and showed obvious attenuation after 50 cycles, with a capacity retention rate of only 84%, indicating poor electrochemical performance.
[0065] Comparative Example 3
[0066] The ratio of electrolyte to electrode particles is the same as that in Example 1. PTFE is used as a binder and conductive carbon black is used instead of carbon nanotubes to prepare the all-solid-state electrode. Electrochemical performance tests were conducted under the same conditions. Figure 7 The results showed that the prepared all-solid-state battery exhibited a discharge capacity of 159.14 mAh / g, with significant attenuation after 50 cycles. Due to the lack of a three-dimensional carbon nanotube cross-linked electron transport network and the increased charge transfer resistance caused by the introduction of a binder, the electrochemical performance was poor.
Claims
1. A method for preparing an all-solid-state composite electrode, characterized in that: The following steps are involved: Step 1: dispersing the carbon material with a solvent to obtain a carbon material dispersion; Step 2: mixing the electrode active material, solid electrolyte and carbon material dispersion according to the mass ratio, and stirring them by ultrasonic and magnetic force to obtain a uniform slurry; Step three: After vacuum filtration of the slurry on the porous current collector, heating and drying, and roller pressing are performed to obtain an all-solid-state composite electrode.
2. The method for preparing an all-solid-state composite electrode according to claim 1, wherein: In the step 1, the solvent is one or more of pentane, hexane, heptane, toluene, p-xylene, chlorobenzene, benzene, acetonitrile, N-methylpyrrolidone, ethers, ethanol, and water.
3. The method for preparing an all-solid-state composite electrode according to claim 1, wherein: In the step 1, the carbon material is one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carboxylated carbon nanotubes, hydroxylated carbon nanotubes, fluorinated carbon nanotubes, graphene, carbon fibers, and fullerenes.
4. The method for preparing an all-solid-state composite electrode according to claim 1, wherein: In the step 2, the mass ratio of the electrode active material, the solid electrolyte, and the carbon material dispersion is 50-80:15-45.5:0.5-5.
5. The method for preparing an all-solid-state composite electrode according to claim 1, wherein: In the step 2, the electrode active material includes a positive electrode material and a negative electrode material, the positive electrode material is one or more of lithium-rich manganese-based materials, lithium iron phosphate, lithium manganate, nickel-cobalt-manganese ternary materials, lithium cobalt oxide, sodium vanadium phosphate, sodium iron pyrophosphate, Prussian compounds, sodium nickel iron manganate, and sodium copper iron manganate, and the negative electrode material is one or more of carbon-based materials, titanium-based materials, silicon-based materials, selenium-based materials, tin-based materials, etc.
6. The method for preparing an all-solid-state composite electrode according to claim 1, wherein: In the step 2, the solid electrolyte is one or more of an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or a halide-based solid electrolyte.
7. The method for preparing an all-solid-state composite electrode according to claim 1, wherein: In the step 2, the ultrasonic power is 100-1500W, the ultrasonic time is 5-30 minutes, and the magnetic stirring time is more than 2 hours.
8. The method for preparing an all-solid-state composite electrode according to claim 1, wherein: In the step three, the porous current collector includes one or more of porous copper foil, porous aluminum foil, composite porous current collector, etc., and the pore size is 10 to 2000 microns.
9. The method for preparing an all-solid-state composite electrode according to claim 1, wherein: In the step 3, the heating and drying temperature is 60-120° C., the heating and drying time is 3-12 hours, and the roller pressing pressure is 3-15 MPa.
10. The all-solid-state composite electrode obtained by the method for preparing an all-solid-state composite electrode according to any one of claims 1 to 9, characterized in that: The invention comprises an electrode active substance, a solid electrolyte and a carbon material. The carbon material is cross-linked to form a three-dimensional conductive network. The electrode active substance and the solid electrolyte are bound on the three-dimensional conductive network.